Utility of recombinant fusion protein ESAT6-CFP10 skin test for differential diagnosis of active tuberculosis: A prospective study - Yuan, Yuan; Xia, Lu; Wu, Qiaoyu; Liu, Xuhui; Lu, Shuihua (Frontiers in Immunology, 2023)
Background The recombinant mycobacterium tuberculosis fusion protein ESAT6-CFP10 skin test (ECST) is a novel test for tuberculosis (TB) infection; however, its accuracy in active tuberculosis (ATB) remains uncertain. This study aimed to evaluate the accuracy of ECST in the differential diagnosis of ATB for an early real-world assessment. Methods This prospective cohort study recruited patients suspected of ATB in Shanghai Public Health Clinical Center from January 2021 to November 2021. The diagnostic accuracy of the ECST was evaluated under the gold standard and composite clinical reference standard (CCRS) separately. The sensitivity, specificity, and corresponding confidence interval of ECST results were calculated, and subgroup analyses were conducted. Results Diagnostic accuracy was analyzed using data from 357 patients. Based on the gold standard, the sensitivity and specificity of the ECST for patients were 72.69% (95%CI 66.8%-78.5%) and 46.15% (95%CI 37.5%-54.8%), respectively. Based on the CCRS, the sensitivity and specificity of the ECST for patients were 71.52% (95%CI 66.4%-76.6%) and 65.45% (95%CI 52.5%-78.4%), respectively. The consistency between the ECST and the interferon-γ release (IGRA) test is moderate (Kappa = 0.47). Conclusion The ECST is a suboptimum tool for the differential diagnosis of active tuberculosis. Its performance is similar to IGRA, an adjunctive diagnostic test for diagnosing active tuberculosis. Clinical trial registration http://www.chictr.org.cn, identifier ChiCTR2000036369.